302 Coverage of automated external defibrillators and volunteer responders according to geographical and demographic characteristics in Denmark. (1st May 2022) - Christensen, NB; Folke, F; Jørgensen, AJ; Jakobsen, LK; Kjoelbye, JS; Gregers, MCT; Ringgren, KB; Andelius, L; Torp-Pedersen, C; Hansen, CM
Abstract : Background: To increase cardiopulmonary resuscitation and defibrillation, many countries have implemented volunteer responder programs to alarm voluntary laypersons in out-of-hospital cardiac arrest (OHCA). This study investigated whether demographic and geographical characteristics were associated with lack of AEDs and volunteer responders. Method: OHCAs from the Danish Cardiac Arrest Registry (2016–2019) with a valid GPS-location were included. OHCA location was assigned to geographical and demographic characteristics defined by Urban Atlas (1) which currently covers 40% (17, 347 km2/42, 933 km2) of Denmark, corresponding to 66% (10, 126/15, 309) of OHCAs from the registry. OHCAs were geocoded into following subgroups: high density residential areas, low density residential areas, public and industrial sites, nature, sport and leisure facilities, transportation, and fast transit roads. OHCAs with missing coverage were defined as OHCA with ≤ 3 volunteer responders or no AEDs within 1, 800 meters. Results: We included 10, 126 OHCAs. In low density residential areas and nature, 5–10% of OHCAs were not covered by AEDs, and 27–46% were not covered by volunteer responders. In contrast, 100% of OHCAs in transportation sites, high density residential areas, and public and industrial sites were covered by AEDs, and 95–99% of OHCA were covered by volunteer responders. Conclusion: Most OHCA (95–100%) in transportation sites, high density residential areas, and public and industrial sites were covered by AEDs and volunteer responders. OHCA coverage varied according to geographical and demographic characteristics supporting continuous focus on tailored AED deployment and volunteer responder recruitment in low density residential areas. Reference: Urban Atlas — Copernicus Land Monitoring Service [Internet]. [cited 2021 Dec 21]. Available from: https://land.copernicus.eu/local/urban-atlas. Conflict of interest: Louise Kollander Jakobsen, Novo Nordisk Foundation, Research Grant. Linn Andelius, Trygfonden, Research Grant. Carolina Malta Hansen, Helsefonden, Trygfonden and Laerdal Foundation, Research Grants. Mads Christian Tofte Gregers, Trygfonden, Resesarch Grant. Nanna Bo Christensen, Trygfonden, Research Grant. Julie Kjølbye, Trygfonden, Research Grant. Christian Torp-Pedersen, Novo Nordisk Foundation, Bayer, Research Grants. Fredrik Folke, Novo Nordisk Foundation, Laerdal Foundation, Research Grants. Funding: Primary investigator of this study, N. Christensen, was supported by research grants from Tryg-Fonden. TrygFonden did not have any influence on data management nor design of the study, and played no role in data collection, analysis, and interpretation of data performed.